STRUCTURAL ORGANIZATION AND PHYSI-OLOGICAL EFFECTS OF VAGS NERVE IN GІТ - Сулаєва О. М. (World of Medicine and Biology, 2015)
The role of vagus nerve in maintaining the structural and functional homeostasis of gastroduodenal is deliberated in the review. The following issues are discussed: characteristics of the afferent vagal nerves in the gastroduodenal area; the effect of vagal afferents in the adaptive response of the gastric and duodenal mucosa; regulation of mucus and acid production by vagal efferent fibers; feedback mechanisms in the control of acid production. Despite the fact that the vagus nerve is a powerful stimulator of the production of hydrochloric acid, it is also determine the activation of cytoprotective mechanisms adapting different structures of gastroduodenal mucosa to peptic factors impact.